Peningkatan Produksi Dan Mutu Tanaman Bayam Merah (Amaranthus Amoena Voss ) Melalui Beberapa Jenis Pupuk Pada Tanah Inceptisols, Desa Pegok, Denpasar - NIRMALAYANTI, KOMANG ARI; SUBADIYASA, I NENGAH NETERA; ARTHAGAMA, I DEWA MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.1, Januari 2017, 2017)
Production Development and Quality Of Red Amaranth(Amaranthus Amoena Voss) Through Some of Type Fertilizer in Inceptisols Land, Faculty of Agriculture Experiment Station, Udayana University This Research aims to know the impact of some of type fertilizer towards the quality and production development of red amaranth in inceptisol land and the chemical characters of Pegok land. This research was conduct in September 2015 until December 2015 at Experiment Station Faculty of Agriculture and Soil Laboratory, Faculty of Agriculture, Udayana University. The Experiment used Randomized Block Design (RBD) and the data analysis used was Costat program. The parameter observed in this research was dividet nto three observations, they were the height of plants, the weight of fresh plants sample, the weight os fresh plants. The plants quality contains of water content and plants storability. The observations of plants chemical characters include pH, KTK, KB, nutrient content N-total, P-avaible, K-avaible, Ca, Mg, C-organic as well as soil electric conductivity. The result of statistical analysis shows that giving some type of fertilization has real impact towards some production parameter and chemical characters but does not give real impact towards water content.
Keywords: Red Amaranth; fertilization; incptisol